Acid-suppressive medications and risk of oesophageal adenocarcinoma in patients with Barrett’s oesophagus: a systematic review and meta-analysis - Singh, Siddharth (2013)
BACKGROUND AND AIMS: Acid-suppressive medications, particularly proton pump inhibitors (PPIs), may decrease the risk of oesophageal adenocarcinoma (OAC) in patients with Barrett’s oesophagus (BO). We performed a systematic review with meta-analysis of studies evaluating the association between acid-suppressive medications (PPIs and histamine receptor antagonists (H2RAs)) and risk of OAC or high-grade dysplasia (BO-HGD) in patients with BO. METHODS: We performed a systematic search of multiple electronic databases and conference proceedings up to June 2013 to identify studies reporting the association between use of acid-suppressive medications and risk of OAC and/or BO-HGD in patients with BO. Summary ORs with 95% CIs were estimated. RESULTS: We identified seven observational studies (2813 patients with BO, 317 cases of OAC or BO-HGD, 84.4% PPI users). On meta-analysis, PPI use was associated with a 71% reduction in risk of OAC and/or BO-HGD in patients with BO (adjusted OR 0.29; 95% CI 0.12 to 0.79). There was a trend towards a dose–response relationship with PPI use for >2–3 years protective against OAC or BO-HGD (three studies; PPI use >2–3 years vs <2–3 years: OR 0.45 (95% CI 0.19 to 1.06) vs 1.09 (0.47 to 2.56)). Considerable heterogeneity was observed. Two studies reported the association between H2RA use and risk of OAC and/or BO-HGD (1352 patients with BO, 156 cases of OAC, 25.4% on H2RAs), and both studies did not show a significant effect. CONCLUSIONS: Based on meta-analysis of observational studies, the use of PPIs is associated with a decreased risk of OAC and/or BO-HGD in patients with BO. None of the studies showed an increased risk of OAC. PPI use should be considered in BO, and chemopreventive trials of PPIs in patients with BO are warranted.